2017
DOI: 10.2147/ott.s118980
|View full text |Cite
|
Sign up to set email alerts
|

Basal oxidative stress ratio of head and neck squamous cell carcinomas correlates with nodal metastatic spread in patients under therapy

Abstract: BackgroundHead and neck squamous cell carcinoma (HNSCC) is a type of cancer that is strongly associated with oxidative damage and oxidative stress. Tobacco and alcohol – sources of massive quantities of reactive oxygen species (ROS) – have been clearly identified as etiologic factors that contribute to these malignancies. Considering the role of glutathione (GSH) in ROS detoxification, we hypothesized that potential biological markers can be found in addition to the parameters of oxidative stress. In line with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
(16 reference statements)
1
10
0
Order By: Relevance
“…In line with previous publications, we believe that parameters of oxidative stress could offer useful potential markers ( 3 , 4 ). Previously, we confirmed this hypothesis by demonstrating that a significant redox imbalance in head and neck cancer patients could offer a prognostic value ( 14 ).…”
Section: Discussionsupporting
confidence: 52%
“…In line with previous publications, we believe that parameters of oxidative stress could offer useful potential markers ( 3 , 4 ). Previously, we confirmed this hypothesis by demonstrating that a significant redox imbalance in head and neck cancer patients could offer a prognostic value ( 14 ).…”
Section: Discussionsupporting
confidence: 52%
“…A recent study, for instance, found a correlation between metastatic spread and basal ROS levels. (1121) Indeed, ROS elevation assists several steps within the advanced oncogenic program, including angiogenesis [in part through stabilizing hypoxia inducible factor (HIF), (1122) avoidance of apoptosis,(1123) and metastasis(1124,1125)]. Several studies link elevated ROS levels to increased disease progression and poor clinical outcomes.…”
Section: Res/ros Signaling In Disease and Therapeutic Interventionsmentioning
confidence: 99%
“…In line with our results, recent data have shown that HNSCC patients with lower oxidative stress had a lower risk of local and regional recurrence of tumor after treatment, suggesting a more aggressive behavior of tumors with high oxidative stress. 50 The efficiency of fundamental DNA repair mechanisms, namely NER and DSB repair, were also evaluated. NER eliminates a broad spectrum of DNA lesions, including those produced by ROS and DNA adducts formed by tobacco smoking and cancer therapeutic drugs such as cisplatin.…”
Section: Discussionmentioning
confidence: 99%